2008
DOI: 10.1525/sop.2008.51.3.563
|View full text |Cite
|
Sign up to set email alerts
|

White Normativity: The Cultural Dimensions of Whiteness in a Racially Diverse LGBT Organization

Abstract: This article builds on examinations of whiteness in organizations by considering how white normativity-or the often unconscious and invisible ideas and practices that make whiteness appear natural and right-is sustained even in organizations that are attentive to structural factors. Based on two years of ethnographic fieldwork, this article critically examines the racial identity and culture of the Center, a Los Angeles lesbian, gay, bisexual, and transgender (LGBT) organization with a national reputation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(90 citation statements)
references
References 13 publications
1
88
0
1
Order By: Relevance
“…Whiteness is mostly used as a concept in US-based studies (Essed & Trienekens, 2008), but our study has shown that incorporating this concept in the study of European (Dutch) organization can provide new insights in minorities' experiences and identity work. It appeared to be a fruitful approach to shed light on whiteness as a cultural formation embedded in organizations (Ward, 2008) which impacts non-white employees. Approaching organizations as 'white' helped to understand how employees with a different religious background than the dominant (atheist or Christian) background fit or do not fit within the organizations in which they are embedded and how they engaged in agency within that space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whiteness is mostly used as a concept in US-based studies (Essed & Trienekens, 2008), but our study has shown that incorporating this concept in the study of European (Dutch) organization can provide new insights in minorities' experiences and identity work. It appeared to be a fruitful approach to shed light on whiteness as a cultural formation embedded in organizations (Ward, 2008) which impacts non-white employees. Approaching organizations as 'white' helped to understand how employees with a different religious background than the dominant (atheist or Christian) background fit or do not fit within the organizations in which they are embedded and how they engaged in agency within that space.…”
Section: Discussionmentioning
confidence: 99%
“…She argued that diversity management could be improved if whiteness was taken into account. This is evidenced by Ward's (2008) study on an L.A.-based LGBT (Lesbian, Gay, Bisexual, Transsexual) center. She showed how white normativity informed the organization's efforts to diversify for the sake of their ethnically heterogeneous target group: The organization's white culture was sustained by its mainstream and corporate approach to diversity rather than becoming diversity-friendly.…”
Section: Whiteness and Diversity Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one of my participants noted that all the gay bars she checked out were not only for gay men, reflecting a dearth of lesbian spaces, but that some had Irish or Italian flags on the outside, which made her unlikely to go inside. Instances like that are an example of how white LGBTQ spaces alienate people of color (Kudler 2007, Ward 2008 in addition to microaggressions (Sue et al 2007, Nadal 2011 and discrimination (for an overview, see Balsam et al 2011, Ghabrial 2016. Facing multiple exclusions, my participants struggled with finding spaces and communities that would safely incorporate all of their identities.…”
Section: Non-religion Paths and Communitymentioning
confidence: 99%
“…33 ○ Take a sexual history and screen for health conditions that are prevalent based on risk behaviors (i.e. HIV) and not on sexual orientation or identity 33 -Nurture commitment to reduce disparities 54,55 -Partner with LGBT community organizations to provide training to all staff on a regular basis 33,39 6. Incentives and Disincentives…”
Section: Patient Flow Through the Care Team / Team Compositionmentioning
confidence: 99%